Analysis of Transmission Phenomena in Low-Potential Heat Transport by Heat Pipes in the Deep- Borehole Simulator - Richard Lenhard; Michal Jakubsky; Milan Malcho; Jozef Jandacka (Communications - Scientific letters of the University of Zilina, 2012)
This article presents a proposal of a simulator for low-potential geothermal heat transfer by means of heat pipes into the heat pump exchanger section. On this device the research on transmission phenomena at different temperatures at the simulator inlet was done. Measurements were taken at various temperature and pressure parameters of carbon dioxide as a working substance in the heat pipe. The paper contains experimental measurements on the simulator for low potential heat transfer and their analysis, theoretical analysis of phase changes in carbon dioxide in the heat pipes depending on changes in pressure and temperature. Simultaneously, the impact of these two quantities on other parameters of the system will be analyzed, namely, input and output temperatures of the coolant in the heat exchanger and cooling of the surrounding rocks. In the conclusion are laboratory results and the CFD simulation model of low-potential geothermal borehole.